PhytoKeys (Pensoft, 2010)
PhytoKeys is a peer-reviewed, open-access journal launched to accelerate research and free information exchange in taxonomy, phylogeny, biogeography and evolution of higher plants and lichens. Journal will publish papers in systematic botany containing taxonomic/floristic data on any taxon of any geological age from any part of the world.